2007
DOI: 10.1111/j.1524-4741.2007.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Tumor Grade and Biological Markers in Locally Advanced Breast Cancer after Chemotherapy ? Implications for a Pathologist

Abstract: There is insurgence of literature evaluating prognostic and predictive factors in breast carcinomas treated with chemotherapy, with a parallel need to develop guidelines for the pathologist interpreting such excisions. Prechemotherapy gun biopsy and postchemotherapy excision specimens from 78 women with locally advanced breast cancer were analyzed for histological changes in the tumor, changes in the tumor grade, hormone receptors, cerb2, and bcl2 and their impact on disease-free survival (DFS). An unusually p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
1
17
1
1
Order By: Relevance
“…The overall frequency of patients with HR status conversion was 16.0%. This incidence of HR status conversion was similar to previous reports on post-NAC change in the ER, PgR, and HER2 statuses, which reported incidences of 8 -28%, 6 -59% (Bottini et al, 1996;Lee et al, 2003;Taucher et al, 2003;Colleoni et al, 2004;Burcombe et al, 2005;Shet et al, 2007;Kasami et al, 2008;Neubauer et al, 2008), and 0 -21% (Bottini et al, 1996;Colleoni et al, 2004;Arens et al, 2005;Burcombe et al, 2005;Quddus et al, 2005;Adams et al, 2008;Kasami et al, 2008;Neubauer et al, 2008), respectively. Although the rate of cases with no change in the HR status after NAC was high, the incidence of change in the HR status is clinically not negligible.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The overall frequency of patients with HR status conversion was 16.0%. This incidence of HR status conversion was similar to previous reports on post-NAC change in the ER, PgR, and HER2 statuses, which reported incidences of 8 -28%, 6 -59% (Bottini et al, 1996;Lee et al, 2003;Taucher et al, 2003;Colleoni et al, 2004;Burcombe et al, 2005;Shet et al, 2007;Kasami et al, 2008;Neubauer et al, 2008), and 0 -21% (Bottini et al, 1996;Colleoni et al, 2004;Arens et al, 2005;Burcombe et al, 2005;Quddus et al, 2005;Adams et al, 2008;Kasami et al, 2008;Neubauer et al, 2008), respectively. Although the rate of cases with no change in the HR status after NAC was high, the incidence of change in the HR status is clinically not negligible.…”
Section: Discussionsupporting
confidence: 76%
“…The hormone receptor (HR) status is one such factor. Although this status is known to change after NAC (Bottini et al, 1996;Lee et al, 2003;Taucher et al, 2003;Colleoni et al, 2004;Burcombe et al, 2005;Shet et al, 2007;Tacca et al, 2007;Kasami et al, 2008;Neubauer et al, 2008), its impact on long-term outcomes has not been assessed. The objective of this retrospective study was to evaluate the frequency and impact of change in the HR status (HR status conversion) on the long-term outcomes in the NAC-administered breast cancer patients.…”
mentioning
confidence: 99%
“…Some studies that used IHC to measure HER2, HER2 status changed in 7.6% to 30.0% of tumors after NCT. 8,[18][19][20][21][22][23][24][25][26] A prospective study that used gene amplification to determine HER2 status found that up to 43% of trastuzumab-treated patients had tumors that had HER2 status discordance after NCT. 27 Similarly, we found that 45.7% of the trastuzumab-treated tumors became HER2-negative.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes some of the published data looking at hormone receptor discordance in this setting. For estrogen receptor status, discordance rates ranging from 2% to up to 57% were observed while that for progesterone receptor discordance ranges from 5.9% to 51% was observed [23][24][25][26][27][28][29][30][31][32][33]. The question that arises is whether the discordance observed is similar among patients who do and do not receive neoadjuvant chemotherapy.…”
Section: Hormone Receptor Statusmentioning
confidence: 99%
“…Table 2 summarizes some of the published studies looking at changes in Her2 status following a course of neoadjuvant chemotherapy. Studies looking at patients who received neoadjuvant chemotherapy without trastuzumab reported discordance in Her2 ranging from 2.3% to 35% when Her2 was tested by IHC and from 2% to 13% when FISH testing determined Her2 status [23,25,28,[30][31][32][33][39][40][41]. Studies that looked at the discordance of Her2 when trastuzumab was incorporated into the neoadjuvant regimen have reported discordance rates of up to 43% when FISH testing determined Her2 status [42][43][44].…”
Section: Her2 Statusmentioning
confidence: 99%